Molecular classification of tumour cells in a patient with intravascular large B‐cell lymphoma. (1st January 2018) - Bauer, W.M.; Aichelburg, M.C.; Griss, J.; Skrabs, C.; Simonitsch‐Klupp, I.; Schiefer, A.I.; Kittler, H.; Jäger, U.; Zeyda, M.; Knobler, R.; Stingl, G.
Summary: Background: Intravascular large B‐cell lymphoma (IVLBCL) is a rare type of extranodal LBCL. It is characterized by the proliferation of tumour cells exclusively intraluminally in small blood vessels of different organs. The clinical manifestation depends on the type of organ affected; additionally, a haemophagocytic syndrome can be observed in some patients. Objectives: The aim was to further understand the nosology of this lymphoma as, due to its rarity and in spite of detailed immunohistochemical investigations, its exact nosology is only incompletely understood. Methods: We used microarray‐based analysis of gene expression of tumour cells isolated from a patient with primary manifestation of the lymphoma in the skin and compared it with various other diffuse LBCLs (DLBCLs) as well as a previously published DLBCL classifier. Results: In unsupervised analyses, the tumour cells clustered together with non‐germinal centre B‐cell (non‐GCB) DLBCL samples but were clearly distinct from GCB‐DLBCL. Analogous to non‐GCB DLBCL, molecular cell‐of‐origin classification revealed similarity to bone‐marrow derived plasma cells. Conclusions: The IVLBCL of this patient showed molecular similarity to non‐GCB DLBCL. Due to the prognostic and increasingly also therapeutic relevance of molecular subtyping in DLBCL, this method, in addition to immunohistochemistry, should also be considered for the diagnosis of IVLBCL in the future.